Predicament of the Scottish Writer: Nationalism and Scottish Literary Criticism in the XX – XXI century - Іваненко, Вікторія Анатоліївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The paper dwells on the notion of “a predicament” of Scottish writer and its reinterpretations in contemporary Scottish criticism. The re-appearance of the notion and its further discussion is connected to the reprint of Edwin Muir’s Scott and Scotland: The Predicament for the Scottish Writer in 1982 for it remained unpublished since 1936. Though Muir’s book was first published at the beginning of the XX century, it became clear that the problem of “a predicament” was still acute in the `80s not only for Scottish literature and criticism, but also for entire Scottish society. The paper highlights the origins and controversies of essentialist nationalistic extrapolations from politics to literature throughout the XX – the beginning of the XXI century.